Dampak Perubahan Harga BBM Terhadap Biaya Operasional Supir Truck Antar Kota dan Provinsi - Suyatin, Febri Ramahdansyah, LCA. Robin Jonathan (EKONOMIA, 2016)
This study aims to determine and analyze the effects of changes in the price of fuel (fuel oil) to the truck driver Operational costs. Formulation of the problem is whether the impact of changes in fuel prices (fuel oil) significantly affects the operational expenses of truck drivers among cities and provinces.The hypothesis in this study is: "change the price of fuel (fuel oil) significantly affects the operational expenses of truck drivers among cities and provinces".The theory used is composed of operational management. Research using interviews as a means of documentation and data collection.The analytical tool used in this study were paired sample t test, with the tools of computer program as SPSS (Statistics Programme For Social Scince) version 20. The results showed operating costs before and after the change the price of fuel (fuel oil) did not differ significantly or may imply changes in the price of fuel (fuel oil) had no significant effect on operating costs.